Deconstructing privilege: Teaching and learning as allies in the classroom - Case, Kim (Routledge, 2013)
Although scholarly examinations of privilege have increased in recent decades, an emphasis on privilege studies pedagogy remains lacking within institutions. This edited collection explores best practices for effective teaching and learning about various forms of systemic group privilege such as that based on race, gender, sexuality, religion, and class. Formatted in three easy-to-follow sections, Deconstructing Privilege charts the history of privilege studies and provides intersectional approaches to the topic. Drawing on a wealth of research and real-life accounts, this book gives educators both the theoretical foundations they need to address issues of privilege in the classroom and practical ways to forge new paths for critical dialogues in educational settings. Combining interdisciplinary contributions from leading experts in the field– such as Tim Wise and Abby Ferber– with pedagogical strategies and tips for teaching about privilege, Deconstructing Privilege is an essential book for any educator who wants to address what privilege really means in the classroom.
Keywords: amériques; approches et analyses; discipline; intersectionnalité; inégalités; justice sociale; outils; ouvrages de références; privilèges; régions géographiques; sciences de l'éducation; systèmes d'oppressions; états-unis

Indigenous youth participatory action research: Re-visioning social justice for social work with indigenous youths - Johnston-Goodstar, Katie (Social Work, 2013)
The NASW Code of Ethics identifies social justice as one of six foundational values of the social work profession. Indigenous communities have long questioned the authenticity of this commitment and rightly so, given the historical activities of social work and social workers. Still, the commitment persists as an inspiration for an imperfect, yet determined, profession. This article presents a theoretical discussion of questions pertinent for social justice in social work practice in Native American communities: Whose definition of social justice should prevail in work with and in Indigenous communities? What can a revisioning of social justice mean to the development of Native communities and for Native youths in particular? What methods or processes of social work are most appropriate for this social justice work? This article presents a case for the practice of youth participatory action research as one method to work for social justice in Native communitie
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; autochtones; discipline; jeunes; justice sociale; périodes historiques; régions géographiques; sciences humaines; thématiques; travail; travail social; états-unis

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes